0
$\begingroup$

My attempt:

  1. Showing that the given map is a homomorphism. Let $a, b ∈ G$ Then, $q(a\circ b) = (a\circ b)\circ N = (a\circ N)\circ(b\circ N) = q(a)\circ q(b)$.
  2. Showing surjectivity [I am stuck up here...]
$\endgroup$
  • $\begingroup$ What's the def of $G/N$ you use? $\endgroup$ – coffeemath Jun 27 at 4:12
  • $\begingroup$ The definition I am using is: (Quotient Group) G/N is the group of all left cosets of N in G. @coffeemath $\endgroup$ – Aakash Singh Bais Jun 27 at 4:16
  • 1
    $\begingroup$ Then if a left coset is $a \circ N$ the map is clearly surjective, you already checked homomorphism. $\endgroup$ – coffeemath Jun 27 at 4:29
2
$\begingroup$

Pick an element (coset) $g N \in G/N$. Then just use $g \in G$ (the coset representative) and $g \mapsto g N$ to give us surjectivity.


Also, I presume you are using epimorphism and surjection interchangeably in the setting of groups, but just for completeness, in the category of groups, we have that a morphism is a surjection if and only if it is an epimorphism, so the fact that this is a surjection shows that it is an epimorphism in $\mathsf{Grp}$.

$\endgroup$
  • $\begingroup$ I am using: Epimorphism = Surjective homomorphism. Is anything wrong in this? $\endgroup$ – Aakash Singh Bais Jun 27 at 4:18
  • 1
    $\begingroup$ No nothing to worry about because in the category of groups, the two notions are the same. They are not the same in other categories however! $\endgroup$ – mathphys Jun 27 at 4:19
1
$\begingroup$
  1. Let $a,b \in G$. Then $$q(ab)=abN=(aN)(bN)=q(a)q(b).$$ That is, $q$ is a group homomorphism.

(Since $N$ is a normal subgroup of $G$,$(aN)(bN)=abN$ multiplication is well-defined.

Because let $x\in(aN)(bN)$. Then $x=an_1 bn_2$ for some $n_1 , n_2 \in N$

Since $N$ is normal, $gN=Ng$ for all $g\in G$. Then $x=an_1 bn_2=a(n_1 b)n_2 =a(b {n'}_1)n_2 =ab{n'}_1 n_2 \in abN$.

Conversely, choosing $a\in aN$ and $b \in bN$, we obtain the coset $abN$.)

  1. Let $\bar g \in G/N$. Then $\bar g = gN$ for some $g\in G$. We choose $g$. Then $q(g)=\bar g=gN$
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.